UPAYA PENINGKATAN KOMPETENSI DASAR MERAKIT DAN MENGURAI KOMPONEN LISTRIK RAMBU CAHAYA PADA SISWA KELAS III TPTL-2 SMK NEGERI 2 CILACAP MELALUI PEMBELAJARAN GRUP INVESTIGASI - Akhmad Mustangin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2011)
This classroom action research is to improve base competence of assembling and disassembling electric component of traffic light. The variable of this research is the improvement of base competence. The researcher used quantitative descriptive statistical analysis with avarage score and percentage in its cycle. The results of this research are (1) there was a 2.7% increase, (2) the students’ activeness in composing the materials increased 5.4%, (3) the students’ activeness in discussion increased 40.54%, and (4) the students’ response increased 0.011% in study problem, 0.159 study club, and 0.078% in group process, in the catagory of agreement was applied group investigation learning model. KewWords: improving base competence through group investigation method.